Suitable Types of Online English Learning to be Implemented at SMPN 3 Tandukkalua - Carles, Carles; Talib, Ahmad; G., Hasriani (State University of Makassar, 2024)
This study aimed to discover suitable types of online learning to be implemented at SMPN 3 Tandukkalua. The researcher applied descriptive qualitative method to achieve the research objective. The data were collected through interview. The subjects of the research were 2 english teachers at SMPN 3Tandukkalua. The subjects were chosen by using purposive sampling technique. Based on the result of the study, the teachers perceived that Asynchronous learning is suitable to be implemented at SMPN 3 Tandukkalua in online English learning. There are some reasons why they chose Asynchronous learning,namely it is flexibel, quick and easy feedback,enhancing learning effectiveness. It is also found that the teaching methods used by the teachers in asynchronous online English learning are Self Directed Learning method combined with Expository method. The use of this method enhance students’activeness in learning,students’ motivation in learning,students’ independence,students’ creativity and problem-solving skill.Keywords: Online learning, Self Directed Learning, Expository method.